MANAJEMEN SUMBER DAYA MANUSIA (Peran Motivasi Guru Terhadap Kreativitas Siswa) - Rahmatullah Rahmatullah (STAI Ma'had Aly Al-Hikam Malang, 2015)
The motivation of teachers in improving student learning creativity. The teacher how you can generate a potential student- to foster a strong sense of encouragement that would give effect to the spirit of learning. Motivation can be summed up in outline arise because of two factors, namely; factors intrinsic and extrinsic factors. Intrinsic factor is faker than in human beings, which can be the attitude, personality, experience, knowledge, ideas. Extrinsic factors are factors outside of man, these factors form a superior style of leadership, encouragement or guidance of someone, the development of the situation and so on. Yet despite the above is different factors, but two factors emerge due to a stimulus. Keatif ideas and thoughts not only come from the imagination and inspiration because history shows that creative ideas are the result of persistent effortKeywords;